DAMPAK MANAJEMEN KEUANGAN RUMAH TANGGA TERHADAP KESEJAHTERAAN KELUARGA - Sukriati (Nusantara Hasana Journal, 2023)
This study aims to determine the impact of household financial management on family welfare. The background of this research is due to the increasing number of divorces that have occurred, especially in the Karang Bedil hamlet, Kediri village, West Lombok, where one of the causes of divorce is due to economic factors. In the household among the many problems that occur, the financial factor is the top factor as the forerunner of the household's prosperity. Problems that occur due to financial factors can be due to excess or lack of money, or a lack of ability to manage or manage finances resulting in expenses exceeding income. In collecting data, researchers used qualitative methods that emphasized the depth of data obtained by researchers by interviewing informants using Simple Random Sampling. The results of this study are that the ability to manage family finances influences household welfare.